Micro-mechanics based pressure dependent failure model for highly cross-linked epoxy resins. (June 2016) - Chevalier, J.; Morelle, X.P.; Bailly, C.; Camanho, P.P.; Pardoen, T.; Lani, F.
Highlights: A new fracture criterion is proposed for highly cross-linked epoxy resins. Fracture initiation is shown to be caused by intrinsic defects. The criterion is only based on two physically-based parameters. The criterion relies on the attainment of a maximum principal stress. The fracture strain is predicted under a large range of stress triaxialities. Abstract: A new fracture criterion for semi brittle epoxy materials is developed, expressed in terms of the attainment of a local critical value of the maximum principal stress at the tip of small internal defects. The criterion is assessed on the highly cross-linked structural epoxy resin RTM6 used as matrix in fiber reinforced composites. Based on finite element simulations of unit cells, the local stress field at the tip of ellipsoidal defects is related to the macroscopic loading. The overall fracture stress levels measured on uniaxial tension and compression specimens are used to identify the two parameters of the failure criterion which involves the characteristic aspect ratio of the microdefects and the critical maximum principal tensile stress. An upper bound to the size of the microdefect is determined based on fracture mechanics arguments. The fracture criterion accurately predicts the fracture for a wide range of stress triaxialities from overall compression conditions to tensile with additional hydrostatic component related to different notched configurations.